Policies and strategies for effective local governance : fiscal autonomy of the district assemblies in Ghana - Djeni, Joseph Osborn (2007)
This thesis focuses on the fiscal autonomy of the District Assemblies in Ghana with the Nzema-East District Assembly being the area of study. It seeks to assess the District Assembly’s own locally generated revenues vis-à-vis the government transfers if such local revenues are sufficiently enough to guarantee financial autonomy to the assembly so as to make the decentralisation concept a reality. It also takes a look at the various mechanisms of local government revenue mobilisation, financial management of the local government finances, assessment of the local treasury and its vulnerability to fraud and the challenges that most local governments encounter with the public in their tax administration. The method used for the study was mainly qualitative methodology which was basically decriptive other than mathematical means but this did not prevent me from the possibility of using quantitative or statistical data to validate my arguments. The methods empirically included interviews, observations, financial statements and reports of the Nzema-East District Assembly. Theoretical literature was used to develop the framework of this research. The findings of this research indicate that the fiscal autonomy of the district assemblies in Ghana have been impeded by some key conflicting policy and legal framework of the decentralisation system in Ghana in that the 1992 Constitution Article 254 is on one hand and other Acts specifically the Financial Administration Act 2003, Act 654, Local Government Service Act 2003, Act 656, Internel Audit Agency Act 2003, Act 658 just to mention a few are also on the other. Most of the local governments’ effective actions toward revenue mobilisation and the free will of their expenditures have been woefully limited by such conflicting legislations and political influences. These legislations are in fact inconsistent with the said Article of the Constitution. Again the findings on the other hand revealed that corruption, fraud, misappropriation and mismanagement of local governments’ funds by public official were co-factors in the impediment of the local governments’ financial autonomy as the continous depletion of local resources through such social vices prevent the district assemblies to take-off financially and independently. Evaluations were made in the conclusion of each chapter with prescription of some recommendations.